Surveillance bronchoscopy in children during the first year after lung transplantation: is it worth it?. Issue 1 (23rd August 2006) - Benden, C; Harpur-Sinclair, O; Ranasinghe, A S; Hartley, J C; Elliott, M J; Aurora, P
Abstract : Background: Since January 2002, routine surveillance bronchoscopy with bronchoalveolar lavage (BAL) and transbronchial biopsy has been performed in all paediatric recipients of lung and heart–lung transplants at the Great Ormond Street Hospital for Children, London, UK, using a newly revised treatment protocol. Aims: To report the prevalence of rejection and bacterial, viral or fungal pathogens in asymptomatic children and compare this with the prevalence in children with symptoms. Participants: The study population included all paediatric patients undergoing single lung transplantation (SLTx), double lung transplantation (DLTx) or heart–lung transplantation between January 2002 and December 2005. Methods: Surveillance bronchoscopies were performed at 1 week, and 1, 3, 6 and 12 months after transplant. Bronchoscopies were classified according to whether subjects had symptoms, defined as the presence of cough, sputum production, dyspnoea, malaise, decrease in lung function or chest radiograph changes. Results: Results of biopsies and BAL were collected, and procedural complications recorded. 23 lung-transplant operations were performed, 12 DLTx, 10 heart–lung transplants and 1 SLTx (15 female patients). The median (range) age of patients was 14.0 (4.9–17.3) years. 17 patients had cystic fibrosis. 95 surveillance bronchoscopies were performed. Rejection (⩾A2) was diagnosed in 4% of biopsies of asymptomatic recipients, and in 12% of biopsies of recipients with symptoms. Potential pathogens were detected in 29% of asymptomatic patients and in 69% of patients with symptoms. The overall diagnostic yield was 35% for asymptomatic children, and 85% for children with symptoms (p<0.001). The complication rate for bronchoscopies was 3.2%. Conclusions: Many children have silent rejection or subclinical infection in the first year after lung transplantation. Routine surveillance bronchoscopy allows detection and targeted treatment of these complications.